Cardiovascular and Renal Morbidity in Takayasu Arteritis: A Population‐Based Retrospective Cohort Study From the United Kingdom. Issue 3 (22nd January 2021) - Goel, Ruchika; Chandan, Joht Singh; Thayakaran, Rasiah; Adderley, Nicola J.; Nirantharakumar, Krishnarajah; Harper, Lorraine
Abstract : Objective: Cardiovascular disease (CVD) is a major complication and cause of mortality in Takayasu arteritis (TAK), but population‐based controlled studies from the UK are lacking. We undertook the present study to investigate the frequency of morbidity and mortality related to CVD, as well as to cerebrovascular and kidney disease, among patients with TAK in the UK. Methods: Yearly cohort and cross‐sectional studies were performed from 2000 to 2017 to estimate annual incidence and prevalence, respectively, of TAK. Using a UK primary care database (IQVIA Medical Research Data), an open retrospective matched cohort study was conducted to estimate risk of hypertension, diabetes, cardiovascular morbidity, chronic kidney disease (CKD), and all‐cause mortality in TAK. Risk (adjusted hazard ratio [HR]) of the assessed comorbidities among patients with TAK compared to age‐ and sex‐matched controls was estimated. Changes in medication prescription over time were examined in both groups. Results: One hundred forty‐two patients with TAK (median age 53.4 years [interquartile range 33.8–70.7]) and 1, 371 matched controls were included. The annual incidence and prevalence of TAK were 0.8 per million and 7.5 per million respectively. All‐cause mortality was increased in TAK (adjusted HR 1.88 [95% confidence interval 1.29–2.76]). Patients with TAK had an increased risk of developing ischemic heart disease, stroke/transient ischemic attack, combined CVD, and peripheral vascular disease compared to controls, but no increase in risk of hypertension, CKD, heart failure, or diabetes. Only ~50% of patients with TAK requiring secondary CVD prevention were prescribed statins or antiplatelet agents within 1 year after study entry. Conclusion: Cardiovascular morbidity was increased among patients with TAK receiving primary care services in the UK. Treatment with statins and antiplatelet agents in these patients was suboptimal.